Determinantes de la exportación de arándanos frescos en el Perú, período 2006-2015 - Sandoval Zamora, Karol Rossy (2016)
The present research has as main objective To determine the main factors that explain the growth in the export of Peruvian fresh blueberries during the years 2006-2015. This will give you a clearer idea of why the growing demand for blueberries not only in Peru but also in the world. The problem is to answer the following question: What are the main factors that explain the growing exports of fresh Peruvian blueberries during the period 2006-2015? The methodology followed, both to obtain information and to analyze the data obtained, involved the use of statistics provided by SIICEX, PROMPERÚ (in relation to national blueberry exports). In addition, publications from state agencies such as the Sierra Exportadora were used to obtain information to better understand the properties and determinants of demand for blueberries. In order to analyze the variables, we used the Microsoft Excel 2013 program and information gathered from research carried out by various authors and institutions, including the three mentioned above. The results show that the main determinants of Peruvian fresh blueberry export are the organic origin of blueberry production, the growing demand for organic products in the world and price levels.